RANCANG BANGUN SISTEM CERDAS PERAWATAN PENCEGAHAN PADA SEKTOR MESIN BUBUT DI BENGKEL MEKANIK POLMANBABEL - Muhammad Rezeki Siti Mariam; Fajar Aswin; Indra Feriadi (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
The maintenance carried out at the Polman Babel Mechanic Workshop uses a breakdown maintenance system. Beakdown maintenance is a maintenance system that is only carried out if a machine is damaged. because it is made preventive maintenance that focuses on scheduling to perform scheduled maintenance on the machine so that it is always ready to use. based on current conditions maintenance activities are still carried out manually. The maintenance system that will be designed uses website technology as a display interface. The stages in designing this system start from problem identification, problem formulation, data collection, system design, system development, testing, analysis, conclusions and suggestions. Based on trial result wich is done by the system design, it will able to generate maintenance schedules, worksheets, and also keep the result of maintenance that have determined when the next treatment will be carried out.